Importance of Integrating Human Factors Engineering in the Oil Industry - Nava Hernández, Ian Carlos (My University, 2024)
This research highlights the significance of applying Human Factors Engineering correctly to enhance safety and ensure successful outcomes in processes using insights from national and international experiences.
Keywords: Petroleum engineering; Human performance; Project planning; Process optimization; Safety culture